Pregnancy and COVID-19: Comparing ICU Outcomes for Pregnant and Nonpregnant Women - Małgorzata Lipińska-Gediga; Waldemar Goździk; Jakub Śmiechowicz; Barbara Adamik (Viruses)
Background: This study compares organ dysfunction, treatment strategies, and unfavorable outcome rates between pregnant and nonpregnant women admitted to the ICU with severe COVID-19, highlighting the increased susceptibility of pregnant women to respiratory infections due to physiological changes. Methods: A retrospective, age-matched study was conducted at a referral center specializing in critical care for pregnant women. Data from 14 pregnant/postpartum and 11 nonpregnant women were analyzed at ICU admission and on days 3, 5, and 7. Results: Acute respiratory distress syndrome was diagnosed in 100% of the pregnant/postpartum group and 64% of the nonpregnant group (p = 0.026). Inflammatory parameters were similar between groups, except for lower ferritin levels in the pregnant/postpartum group compared to the nonpregnant (120 vs. 568 µg/L at admission and 90 vs. 616 µg/L on day 3). Creatinine, lactate, and lactate dehydrogenase levels were significantly lower in the pregnant/postpartum group. A reduction in the SOFA score was observed over time in the pregnant/postpartum group (from 7.0 to 4.0 points, p = 0.009), while no change was noticed in the nonpregnant group (from 3.0 to 2.5 points, p = 0.181). Unfavorable outcome rates were similar, with two patients from each group succumbing to the disease (p = 0.604). Conclusions: The findings suggest that pregnancy does not increase the risk of unfavorable outcomes among women with severe COVID-19 receiving ICU treatment. However, additional studies with larger sample sizes are needed to validate these observations.